Application of Direct and Indirect Non-thermal Plasma in the Development of Ready-to-Eat Foods - Denoya, Gabriela Inés; Szerman, Natalia; Vaudagna, Sergio Ramon (Springer Nature, 2024)
Purpose of Review: The studies of the application of non-thermal plasma (NTP) for food processing and preservation during the last 5 years have been exponentially increasing. In this work, we review the main findings in NTP application in foods to discern which aspects are lacking to achieve innovation for a successful transfer to the food industry. Recent Findings: NTP was first proven in foods as a technology for reducing microbial load. However, novel applications of the NTP include the reduction of additives and agrochemical residues, the use as a pre-treatment for drying, the improvement of functional properties, and even for the modulation of sensorial characteristics. Summary: In this work, we summarize the fundamentals of the NTP, the main effects on microorganisms and food components, and the novel applications for ready-to-eat fruit, vegetable, and meat products.